Peningkatan Pengetahuan Orang Tua Dalam Pola Didik Anak Yang Benar Melalui Sosialisasi Pola Asuh Di Desa Ranah Sungkai Kec. XIII Koto Kampar Kabupaten Kampar - Rahmatullah Rahmatullah; Merri Silvia Basri; Martiana Bella (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
Good parenting will result in the formation of good morals, principles and behavior in children now and in the future. Parents are the main factor in creating children's morals, principles and behavior in living life. Parents provide parenting patterns to children in the form of physical or personal treatment, namely words, attitudes, behavior and actions carried out by parents. Children will adapt and become familiar with the surrounding environment and the interactions with fellow humans that children will have through the parenting style provided by their parents. The family teaches good education which plays an important role in the growth and development of the child's personality The attitude shown by parents can determine family relationships because once a relationship has been formed it tends to last. Parents must be able to understand their children well and recognize their children's attitudes and desires in developing and educating their children without forcing them to be someone else. Interactions carried out between parents and children should not use threatening and judgmental actions but should be diverted to words that tend to be advice or motivational so that children can achieve success in developing good character., authoritarian, indulgent and neglectful parenting.